Multiple recombination events between endogenous retroviral elements and feline leukemia virus - Ngo, Minh Ha; AbuEed, Loai; Kawasaki, Junna; Oishi, Naoki; Pramono, Didik; Kimura, Tohru; Sakurai, Masashi; Watanabe, Kenji; Mizukami, Yoichi; Ochi, Haruyo; Anai, Yukari; Odahara, Yuka; et al. (Journal of virology, 2024)
Feline leukemia virus subgroup A (FeLV-A) is primarily transmitted among cats. During viral transmission, genetic changes in the viral genome lead to the emergence of novel FeLV subgroups or variants with altered virulence. We isolated three FeLV subgroups (A, B, and D) and XR-FeLV from two cats and identified multiple recombination events in feline endogenous retroviruses (ERVs), such as enFeLV, ERV-DC, and FcERV-gamma4, which are present in the cat genome. This study highlights the pathogenic contribution of ERVs in the emergence of FeLV-B, FeLV-D, and XR-FeLV in a feline population.